Evaluación de la recuperación de Suelos en Taludes de terrazas de Banco con Pasto Milín (phalaris tuberosa), aplicando dos tipos de Abonos y cuatro distancias de siembra en Salache, Cotopaxi. - Gutiérrez Navas, Daniel Gonzalo (2020)
The research took place at the Salache Experimental Center (CEASA), at coordinates X: 0764249, Y: 9889461 at 2734 masl, with the topic Evaluation of soil recovery on bank terraces slopes with milin grass (Phalaris tuberosa), applying two types of fertilizers and four planting distances in Salache, Cotopaxi. The objectives in this study were: To evaluate the density of plantation and optimal organic fertilizer for the performance of Milín grass (Phalaris tuberosa) in the recovery of soils on slopes; study agronomic variables between treatments; Analyze the physical-chemical values of the soil for each treatment, to carry out the objectives, a completely randomized block design (DBCA) with twelve treatments and three repetitions was proposed, giving a total of thirty-six experimental units. The results of the research revealed that when applying organic matter the percentage of macro nutrients (NPK) increased, at the beginning of the study a soil with low levels was found and at the end a considerable increase in these values was obtained, the percentage of organic matter had an increase from 1.00% at the beginning to 1.6% at the end, the pH had a change in alkalinity from 10.40 at the beginning, to 9.71 at the end of the study, the best treatment given in terms of growth was the ecoabonaza application after 90 days of data collection. It is worth highlighting the production of milin grass in soils with these edaphic characteristics as socioeconomic alternatives in the area, since their adaptability and resistance to edaphoclimatic conditions is an advantage for the use and conservation of the existing soils in this area, not only at the level provincial but at the national level.